THE SECRETS TO MASTERING ACADEMIC WRITING SKILLS: FORMAL STYLE, CRAFTING A STRONG THESIS STATEMENT, AND RULES FOR AVOIDING PLAGIARISM. - Ravshanova Marjona Jumaniyoz qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
ABSTRACT: This article provides essential strategies and actionable rules for students  and  researchers  aiming  to  elevate  their  academic  writing  skills  to  meet international standards. Effective academic communication requires a balance between formal language, clear argumentation, and unwavering integrity. The  paper  first  explores  the  principles  of  Formal  Style,  emphasizing  the necessity  of  objectivity,  clarity,  and  the  judicious  use  of  sophisticated  academic vocabulary, while advising against personal pronouns and emotional language. Next, it delves into the core of any scholarly work: the Thesis Statement. Practical guidelines are offered on how to craft a thesis that is debatable, specific, and focused, serving as the central argument of the entire paper. Finally, the article provides a critical review of  Rules  for  Avoiding  Plagiarism,  distinguishing  between  direct  quoting,  effective paraphrasing, and summarizing. It underscores the importance of proper in-text citation using recognized formats (e.g., APA/MLA) to uphold academic honesty. By mastering these three pillars—formal expression, strong argumentation, and ethical referencing—authors can ensure their research is not only impactful but also credible and academically rigorous.